Natural history and treatment of hepatitis B virus and hepatitis C virus coinfection - Keeffe Emmet B; Crockett Seth D (BMC, 2005)
Abstract Hepatitis B virus (HBV) and hepatitis C virus (HCV) coinfection is not uncommon as a result of similar routes of infection. Patients who are coinfected represent a unique group with diverse serologic profiles. Combined chronic hepatitis B and C leads to more severe liver disease and an increased risk of hepatocellular carcinoma. Furthermore, coinfected patients represent a treatment challenge. No standard recommendations exist for treatment of viral hepatitis due to dual HBV/HCV infection, and therefore treatment must be individualized based on patient variables such as serologic and virologic profiles, patient's prior exposure to antiviral treatment, and the presence of other parenterally transmitted viruses such as hepatitis D virus and human immunodeficiency virus. The natural history and treatment of patients with HBV and HCV coinfection is reviewed.